"dx(y\\sin2x)=(1+y^2+\\cos^2 x)dy\\\\\ny\\sin2xdx-(1+y^2+\\cos^2 x)dy=0\\\\\nP=y\\sin 2x\\\\\nQ=-(1+y^2+\\cos^2 x)\\\\\n\\frac{\\partial F}{\\partial y}=\\sin2x\\\\\n\\frac{\\partial Q}{\\partial x}=-2\\cos x(-\\sin x)=\\sin 2x"
Then "\\exist" function "u(x,y)" :
"\\frac{\\partial u}{\\partial x}=P=y\\sin 2x\\\\\n\\frac{\\partial u}{\\partial y}=Q=-(1+y^2+\\cos^2 x)\\\\\nu(x,y)=\\int y\\sin2xdx=-\\frac{1}{2}y\\cos2x+\\psi(y)\\\\\n\\frac{\\partial u}{\\partial y}=-\\frac{1}{2}\\cos2x+\\psi'(y)=\\\\\n=-\\frac{1}{2}(2\\cos^2x-1)+\\psi'(y)=\\\\\n=-\\cos^2x+0.5+\\psi'(y)\\\\\n-\\cos^2x+0.5+\\psi'(y)=-1-y^2-\\cos^2x\\\\\n\\psi'(y)=-1.5-y^2\\\\\n\\psi(y)=-1.5y-\\frac{y^3}{3}"
Then
"u(x,y)=-0.5y\\cos2x-1.5y-\\frac{y^3}{3}"
solution of equation is
"-0.5y\\cos2x-1.5y-\\frac{y^3}{3}=c"
Comments
Leave a comment